Phosphodiesterases : CNS functions and diseases - Zhang, Han-Ting; Xu, Ying; O'Donnell, James M. (Springer, 2017)
PDEs are a family of enzymes that catalyze the hydrolysis of intracellular cyclic neucleotides. They are implicated in a number of disorders and dysfunctions and PDE inhibitors have already proven to be effective therapies for erectile dysfunction, COPD, and psoriatic arthiritis. This family of enzymes also plays a role in diseases and disorders of the CNS such as depression, anxiety, schizophrenia, and Alzheimer's Disease. Unfortunately no effective PDE inhibitors have been developed for the treatment of these diseases. The proposed book will be a comprehensive overview of the current state of basic and translational research on PDE inhibitors written by internationally recognized experts. Authors will also discuss potential PDE subtypes and splice variants in the hopes that this will spur more creative approaches to PDE targeting drugs.
Keywords: Phosphodiesterases.; Nervous system -- Diseases -- Molecular aspects.; elektronické knihy; electronic books